Legal Pluralism in the Tayade System: Reconciling Land and Plant Ownership Laws in Gorontalo - Lahaling, Hijrah; Rahim, Arhjayati; Beddu, Sumiyati; Aribah, Dzikra Ridha Dwi; Saharuddin, Saharuddin (IAIN Manado, 2025)
This study examines the legal uncertainty surrounding the Tayade land and tree transaction system in Gorontalo, Indonesia, which lacks formal regulations under both positive and Islamic law. The Tayade system separates ownership rights between land and vegetation, resulting in dual ownership over a single plot. This research explores solutions to the dual ownership issue and its implications for land and tree owners. A comparative approach with descriptive methods was used, analyzing land and tree transaction rules from positive and Islamic law perspectives through a literature review. The findings reveal that the absence of clear regulations creates legal uncertainty and potential conflicts due to inconsistencies between Tayade customary law, positive law, and Islamic law. The study concludes that harmonizing these legal systems is essential for effectively managing land and vegetation rights. Such harmonization would strengthen legal certainty and reduce conflicts in transferring rights under the Tayade system. The study recommends the development of more specific regulations to govern the practice, ensuring more transparent and more appropriate legal frameworks for the community.